Anteseden Dari Purchase Intention Yang Dimediasi Oleh Brand Equity Pada Uniqlo - Lutfan Ramadhan; Ganawati Ganawati (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this study was to determine what factors affect purchase intention with the variables used are surveillance, social interaction, information sharing, remuneration, entertaintment, and brand equity. This study used a purposive sampling technique with 134 samples with the criteria that consumers have purchased product at Uniqlo at least 3 times in the last 6 months. The tool used in this research is Structural Equation Model (SEM) to analyze complex variable relationships that are run by the AMOS program. The results of this study indicate that there is a negative effect of surveillance on brand equity, there is a positive effect of social interaction on brand equity, there is a positive effect of information sharing on brand equity, there is a negative effect of remuneration on brand equity, there is a positive effect of entertaintment on brand equity, there is a positive effect of brand equity on purchase intention.